Giulio II: da ’papa Guerriero’ a ’papa Penitente’ - Forcellino, Maria (Incontri. Rivista europea di studi italiani, 2017)
Julius II from ‘Warrior Pope’ to ‘Penitent Pope’ This article discusses the commission and meaning of the tomb monument of Pope Julius II (1503-1513), with a focus on the statue representing the pope himself. In 1505, when Julius II ordered Michelangelo to make this monument, it was quite uncommon that a pope would commission his own tomb, as this was considered the duty of one or more family members. According to Michelangelo’s biographers, Vasari and Condivi, Julius II wanted an impressive, free standing monument, inspired by ancient mausoleums, to be placed in the new basilica of St. Peter, but a few years later Julius II seems to have changed his mind. After his death in 1513, his descendants took care of the tomb project, which in the end took forty years to complete and was finally erected in 1544, in the church of San Pietro in Vincoli. The monument that was finally realized is actually a cenotaph and is an abbreviated version of the tomb as it was originally planned. It is not free standing, but is placed against the back wall of the right transept. Michelangelo’s interpretation of a funerary wall monument has resulted in a very original design, both architecturally and iconographically. He created an iconographic program with seven sculptures including two new religious figures, Active Life and Contemplative Life. On the top in the middle of the monument a statue (made between 1533 and 1542) represents Julius II in a singular pose, which approximates the demi-gisant type that was common in the years 1500-1530. An iconographic analysis of the statue, especially of the face and the ecclesiastical clothes, reveals that Julius II is characterized more as a ‘Penitent Pope’ than as the ‘Warrior Pope’ he historically was. The conclusion is that this specific portrayal of the pope was the artist’s choice rather than Julius’s. It reflects Michelangelo’s religious attitude and his spiritual believe in the final period of his life.